LA UTILIZACIÓN DE LA BIO POR LOS PROGRAMAS DE LA RADIO ESPAÑOLA EN TWITTER. DE LA PRESENTACIÓN DEL PERFIL A LA RADIO TRANSMEDIA. - Teresa PIÑEIRO OTERO (Fonseca, Journal of Communication, 2023)
The jump of conventional radio programs into social media has evolved in new spaces and interaction forms between radio broadcasters and radio listeners. Particularly, twitter community acquires a new dimension due to its public (non privacy status) and shareability